Probing temperature‐ and solvent‐dependent protein dynamics using terahertz time‐domain spectroscopy. (4th February 2014) - Tych, Katarzyna M.; Wood, Christopher D.; Burnett, Andrew D.; Pearson, Arwen R.; Davies, A. Giles; Linfield, Edmund H.; Cunningham, John E.
<x xml:space="preserve">Abstract</x> The effect of temperature on the terahertz‐frequency‐range material properties of lyophilized and single‐crystal hen egg‐white lysozyme has been measured using terahertz time‐domain spectroscopy, with the results presented and discussed in the context of protein and solvent dynamical and glass transitions. Lyophilized hen egg‐white lysozyme was measured over a temperature range from 4 to 290 K, and a change in the dynamical behaviour of the sample at around 100 K was observed through a change in the terahertz absorption spectrum. Additionally, the effect of cryoprotectants on the temperature‐dependent absorption coefficient is studied, and it is demonstrated that terahertz time‐domain spectroscopy is capable of resolving the true glass transition temperature of single‐crystal hen egg‐white lysozyme at ∼150 K, which is in agreement with literature values measured using differential scanning calorimetry.